Local Current Through Helical Orbitals - Hyllested, Louise Oxen Høgh (UCPH NanoScience - a student research journal, 2018)
Traditional chemical research has given great information about the physical properties of molecules. This research provides understanding of how molecules work in the classical ways, but the limit is reached when molecules are used in a non-traditional way. Now molecules can be inserted in molecular junctions, which makes it possible to examine molecules in new ways. Recent theoretical work has shown that some linear molecules can have helical orbitals. Here the question of interest is whether the current density around these particular molecules are affected by the helical orbitals and the coupling of the electrodes. We show that the helical orbitals in combination with the coupling of the electrodes, indeed has an impact on the current and that the orbitals contribute to a circular current around these linear molecules. As the understanding of the currents behavior around the molecules expand, it paves the way for new chemical questions about how we can control the current. For example, how helical current may induce magnetic properties in non-magnetic molecules, and how chemical substituent can be used to impact these effects.